Perspectives on Oncolytic Salmonella in Cancer Immunotherapy—A Promising Strategy - Wang, Ding; Wei, Xiaodong; Kalvakolanu, Dhan V.; Guo, Baofeng; Zhang, Ling (Frontiers in Immunology, 2021)
Since the first reported spontaneous regression of tumors in patients with streptococcus infection, cancer biological therapy was born and it evolved into today’s immunotherapy over the last century. Although the original strategy was unable to impart maximal therapeutic benefit at the beginning, it laid the foundations for the development of immune checkpoint blockade and CAR-T which are currently used for cancer treatment in the clinics. However, clinical applications have shown that current cancer immunotherapy can cause a series of adverse reactions and are captious for patients with preexisting autoimmune disorders. Salmonellae was first reported to exert antitumor effect in 1935. Until now, numerous studies have proved its potency as an antitumor agent in the near future. In this review, we summarize the currently available data on the antitumor effects of Salmonella, and discussed a possibility of integrating Salmonella into cancer immunotherapy to overcome current obstacles.